Managing underground transfer of floods for irrigation: a case study from the Ramganga Basin, India - Reddy, V.R.; Rout, S.K.; Shalsi, Sarah; Pavelic, Paul; Ross, A. (Elsevier, 2020)
Protecting flood prone locations through floodwater recharge of the depleted aquifers and using it for protecting dry season irrigated agriculture is the rationale for a form of intervention termed as ‘underground transfer of floods for irrigation’ (UTFI). This helps reduce the intensity of seasonal floods by tapping and storing excess floodwater in aquifers for productive agricultural use. This paper presents a case study of managing the recharge interventions in the context of the Ramganga basin, India. Using a case study approach, this study determines the socio-economic and institutional context of the study area, proposes three potential routes to institutionalize UTFI, and provides insights for scaling up the interventions in the Ganges and other river basins that face seasonal floods and dry season water shortages. Managing the interventions involves community participation in regular operations and maintenance tasks. Given the limited scale of the pilot UTFI intervention implemented to date, and the socio-economic and institutional context of the case study region, the benefits are not conspicuous, though the piloting helped in identifying potential ways forward for the long-term management of the pilot site, and for scaling up the interventions. Initially pilot site management was handled by the project team working closely with the community leaders and villagers. As the intervention was demonstrated to perform effectively, management was handed over to the district authorities after providing appropriate training to the government personnel to manage the system and liaise with the local community to ensure the site is operated and managed appropriately. The district administration is willing to support UTFI by pooling money from different sources and routing them through the sub-district administration. While this is working in the short term, the paper outlines a programmatic longer term approach for wider replication.